2023
DOI: 10.3389/fpls.2023.1192818
|View full text |Cite
|
Sign up to set email alerts
|

Use of Trichoderma culture filtrates as a sustainable approach to mitigate early blight disease of tomato and their influence on plant biomarkers and antioxidants production

Abstract: IntroductionAlternaria solani is a challenging pathogen in the tomato crop globally. Chemical control is a rapid approach, but emerging fungicide resistance has become a severe threat. The present study investigates the use of culture filtrates (CFs) of three species of Trichoderma spp. to control this disease.MethodsHighly virulent A. solani strain and three Trichoderma fungal strains viz., T. harzianum (Accession No: MW590687), T. atroviride (Accession No: MW590689) and T. longibrachiatum (Accession No: MW59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Singh and coworkers [58] reported that the protection of sunflower plants afforded by T. harzianum against Rhizoctonia solani was associated with the accumulation of antioxidants including phenolic compounds that played a crucial role in counteracting the oxidative stress produced by the pathogen attack. Similarly, the accumulation of phenolic compounds and other antioxidants induced by treatment with T. harzianum reduced the severity of early blight disease in tomato plants [15] and alleviated the oxidative stress caused by the Fusarium crown rot disease in durum wheat [33].…”
Section: Accumulation Of Phenolic Compounds and Antioxidant Activity ...mentioning
confidence: 98%
See 1 more Smart Citation
“…Singh and coworkers [58] reported that the protection of sunflower plants afforded by T. harzianum against Rhizoctonia solani was associated with the accumulation of antioxidants including phenolic compounds that played a crucial role in counteracting the oxidative stress produced by the pathogen attack. Similarly, the accumulation of phenolic compounds and other antioxidants induced by treatment with T. harzianum reduced the severity of early blight disease in tomato plants [15] and alleviated the oxidative stress caused by the Fusarium crown rot disease in durum wheat [33].…”
Section: Accumulation Of Phenolic Compounds and Antioxidant Activity ...mentioning
confidence: 98%
“…It is generally assumed that Trichoderma spp. may induce the plant to shift from primary to secondary metabolism with the consequent accumulation of secondary metabolites of phenolic nature [13][14][15]. The buildup of these compounds may serve as an antioxidant defense mechanism that protects the plant tissues from the oxidative stress triggered by pathogen attack [16], but it also increases the nutraceutical value of treated plants [17].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of Trichoderma isolates on electrolyte leakage of P. aphanidermatum was studied as described previously [63,64]. 5 mm mycelial discs of Trichoderma isolates (3-dayold, previously grown on PDA) were transferred into 50 mL sterile conical flasks containing 5 of 16 25 mL potato dextrose broth (PDB, Sigma Aldrich, MO, USA) and, subsequently, incubated at 27 • C in a shaker for 7 days.…”
Section: Effect Of Trichoderma Isolates On Extracellular Conductivity...mentioning
confidence: 99%
“…In fully scan acquisition mode, the Electron Impact (EI) mass scan (m/s) range was 40-450 Da. (Muhammad et al, 2023).…”
Section: Characterization Of Secondary Metabolites From Optimized Cul...mentioning
confidence: 99%